Rumors, Conspiracies and the Psychological Climate of World Politics - Thompson, W. Scott (Tufts Archival Research Center, 2005)
Volume 22, Issue 1. Winter/Spring W. Scott Thompson reflects on the psychological climate of paranoia and suspicion that has shaped perceptions of the American persona and the CIA.